Metronomic chemotherapy with the COMBAT regimen in advanced pediatric malignancies: a multicenter experience - Zapletalova, D; André, N; Deak, L; Kyr, M; Bajciova, V; Mudry, P; Dubska, L; Demlova, R; Pavelka, Z; Zitterbart, K; Skotakova, J; Husek, K; et al. (Oncology, 2012)
BACKGROUND: The outcome of children with refractory/relapsed malignancies remains poor and novel therapies are urgently required. One of the promising approaches is metronomic chemotherapy. We present the clinical results of 74 children with advanced solid tumors treated according to treatment recommendation with data registry in three European pediatric centers. METHODS: COMBAT (Combined Oral Metronomic Biodifferentiating Antiangiogenic Treatment) included low-dose daily temozolomide, etoposide, celecoxib, vitamin D, fenofibrate and retinoic acid. From 2004 to 2010, 74 children were enrolled. RESULTS: The 2-year overall survival (OS) was 43.1% (median 15.4, range 1.3-69.9 months). Of the 74 patients, 50 patients (68%) died and 24 are alive: 6 (8%) with progressive disease, 7 (9%) with stable disease/partial response and 11 (15%) in complete response. Median time to response was 6 months. Of 62 patients with initially measurable disease, 25 (40%) had radiological response or stable disease. Fourteen of 25 showing clinical benefit responded within the first 6 months. The treatment was well tolerated on an outpatient basis. Regarding non-hematological toxicity of grade ≥2, hepatotoxicity of grade 3 occurred in 8 children and grade 3 cheilitis in 16 children. CONCLUSION: COMBAT is a feasible and effective treatment option for patients with relapsing/refractory malignancies. The treatment is well tolerated with a low acute toxicity profile.
Keywords: Young Adult; Sulfonamides; Temozolomide; Male; Child, Preschool; Neoplasms; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; Adolescent; Isotretinoin; Infant; Child; metronomické podávání léků; isotretinoin; temozolomid; Europe; Fenofibrate; dítě; Adult; Pyrazoles; dospělí; etoposid; mužské pohlaví; registrace; vitamin D; celekoxib; mladiství; Evropa; předškolní dítě; Dacarbazine; Angiogenesis Inhibitors; lidé; Celecoxib; ženské pohlaví; Humans; inhibitory angiogeneze; protokoly protinádorové kombinované chemoterapie; dakarbazin; kojenec; Administration, Metronomic; nádory; fenofibrát; Registries; Vitamin D; Female; pyrazoly; sulfonamidy; studie proveditelnosti; Etoposide; Feasibility Studies